AB0141 Porphyromonas Gingivalis Enhances Citrullination in Collagen Induced Arthritis. (9th June 2015) - Jung, S.M.; Koh, J.H.; Min, H.K.; Lee, J.Y.; Lee, J.; Kim, J.H.; Kwok, S.-K.; Park, K.-S.; Yoon, C.-H.; Park, S.-H.; Ju, J.H.
Abstract : Background: The association of rheumatoid arthritis (RA) and periodontal disease is supported by many epidemiologic studies. P. gingivalis, a pathogenic organism in periodontal disease, can be a link between two diseases via citrullination. Objectives: This study was conducted to investigate the pathogenic effect of P. gingivalis on autoimmune arthritis in vivo . Methods: We compared the clinical and histological characteristics in collage-induced arthritis (CIA) mice infected with or without P. gingivalis . W83 strain of the anaerobic bacteria was intraperitoneally injected twice a week to simulate the chronic infection. Clinical evaluation and routine histological analysis were performed in the experimental groups. In addition, the joint sections of CIA mice were immunostained with anti-citrullinated peptide antibodies (ACPAs) produced by hybridoma cell lines (12G1) reactive to cyclic citrullinated peptide. The areas stained with ACPAs were measured by computerized system for quantitative image analysis. Results: Infection with P. gingivalis exacerbated clinical arthritis in CIA mice. Histological analysis also revealed aggravation of synovial inflammation and bone destruction in CIA mice infected with P. gingivalis . Accordingly, TRAP positive cells were more abundant in synovial tissues of the infected CIA mice. Citrullination of tissue was prominently shown in RA synovium than osteoarthritis by 12G1 ACPA. Citrullination was detected in all of CIA mice, while ACPA-positive area was absent in wild type mice infected with P. gingivalis . Citrullinated area determined by staining with ACPA was more extensive in CIA mice infected with P. gingivalis compared to control CIA mice. Conclusions: This result suggests that P. gingivalis might aggravate autoimmune arthritis by overproduction of citrullinated antigen. Citrullination mediated by P. gingivalis can be a possible mechanism bridging a gap between periodontal disease and RA. References: Koziel, J., P. Mydel, and J. Potempa, The link between periodontal disease and rheumatoid arthritis: an updated review. Curr Rheumatol Rep, 2014. 16(3): p. 408. Maresz, K.J., et al., Porphyromonas gingivalis facilitates the development and progression of destructive arthritis through its unique bacterial peptidylarginine deiminase (PAD). PLoS Pathog, 2013. 9(9): p. e1003627. Acknowledgements: This work was supported by a grant from the Korea Healthcare Technology R&D Project, Ministry for Health, Welfare & Family Affairs, Republic of Korea (A092258). Disclosure of Interest: None declared